Co-precipitation vs. Green Synthesis: A Comparative Analysis of Structure, Morphology, Optical Properties, and Antibacterial Activity of Ag/ZnO Nanocomposite - Lakshmi, S. Magara Jothi; Rejith, S. G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Ag/ZnO nanocomposites were successfully prepared through co-precipitation (CS) and a green synthesis (GS) route mediated by Moringa Oleifera. The confirmation of their formation was evident from the simultaneous presence of Ag and ZnO reflections in powder X-ray diffraction. Field emission scanning electron microscopy (FESEM) analysis disclosed an average particle size of approximately 22 nm and 146 nm for CS and GS samples, respectively. The CS sample exhibited a disstinctive flower-like morphology, indicating a unique self-assembly and growth pattern, while the GS sample displayed an almost rectangular shape. Structural composition and functional groups in the nanocomposites were analyzed using FT-IR spectroscopy. The direct band gaps were determined as 3.12 eV for CS and 3.10 eV for GS samples using a Tauc plot derived from UV-Vis NIR spectrometry. Notably, the antibacterial evaluation of the green-synthesized Ag/ZnO exhibited a pronounced zone of inhibition against both gram-positive (S. aureus) and gram-negative (E. coli) bacteria, demonstrating superior efficacy compared to chemically prepared Ag/ZnO. Overall, the study highlights the successful synthesis, structural characterization, and enhanced antibacterial properties of Ag/ZnO nanocomposites via a green route mediated by Moringa Oleifera. GRAPHICAL ABSTRACT